HD 226766: a hierarchical SB3 system with two twin Am stars. Issue 1 (14th May 2019) - Catanzaro, G; Gangi, M; Giarrusso, M; Munari, M; Leone, F
ABSTRACT: In this paper, we present a detailed revision of the orbital parameters and the first quantitative abundance analysis of the spectroscopic triple system HD 226766. By means of a simultaneous fit of the radial velocities of all the three components, we derived precise orbital parameters for the system, in particular inner pair has P (d)  =  31.9187 ± 0.0001, e   =  0.28 ± 0.01, and M A / M B   = 1.03 ± 0.03, while the C component orbits around the inner pair with a period of P (d)  =  1615 ± 59 in a very eccentric orbit ( e   =  0.54 ± 0.11). From the fit of the Hβ and Hα profiles, we determined the effective temperatures and surface gravities of each component of the inner pair: T eff   =  8600 ± 500 K and log  g   =  3.8 ± 0.2 for HD 226766 A and T eff   =  8500 ± 400 K and log  g   =  4.0 ± 0.2 for HD 226766 B. In the hypothesis that component C is a main sequence star (log  g   =  4.0) we derived T eff   =  8000 ± 500 K. Rotational velocities have been estimated by modeling the profiles of metallic lines: v sin  i   =  13 ± 1 km s −1 for inner pair and v sin  i   =  150 ± 20 km s −1 for the C component. We find that the inner pair is heterogeneous from the point of view of the chemical composition: both stars are very similar and show chemical anomalies typical of Am stars. With some hypothesis about the masses of the components, we estimated the orbital inclination angle for the inner binary, i  = (47 ± 1) ○, and for the outer orbit, i  = (54 ± 19) ○ .